2021
DOI: 10.3390/molecules26133948
|View full text |Cite
|
Sign up to set email alerts
|

An Overview on Total Valorization of Litsea cubeba as a New Woody Oil Plant Resource toward a Zero-Waste Biorefinery

Abstract: With the increasing global demand for edible oils and the restriction of arable land minimum in China, woody oil plants have gradually become the optimal solution to cover the shortage of current edible oil supply and to further improve the self-sufficiency rate. However, due to the lack of knowledge and technique, problems like “how to make full use of these plant resources?” and “how to guide consumers with reasonable data?” limit the development of woody oilseed industry towards a sustainable circular econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 89 publications
0
1
0
Order By: Relevance
“…Likewise, Liu et al (2014) reported that under optimal conditions, the yield of ultrasonic-assisted extraction of L. cubeba oil reached up to 41.4%; fruit-containing seeds were used as raw material; therefore, the contribution of kernel oil to the extraction rate cannot be ignored. The other study that actually investigated the technological conditions of supercritical CO 2 fluid technique in extracting L. cubeba kernel oil (Zhang et al, 2000) was mistakenly referenced as an LCEO extraction study in the review paper (Qiu et al, 2021). To clear up the confusion, we provide an updated and detailed description on methods for extracting L. cubeba oil (essential oil and kernel oil) in Table 1.…”
Section: Extraction Of Lceomentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Liu et al (2014) reported that under optimal conditions, the yield of ultrasonic-assisted extraction of L. cubeba oil reached up to 41.4%; fruit-containing seeds were used as raw material; therefore, the contribution of kernel oil to the extraction rate cannot be ignored. The other study that actually investigated the technological conditions of supercritical CO 2 fluid technique in extracting L. cubeba kernel oil (Zhang et al, 2000) was mistakenly referenced as an LCEO extraction study in the review paper (Qiu et al, 2021). To clear up the confusion, we provide an updated and detailed description on methods for extracting L. cubeba oil (essential oil and kernel oil) in Table 1.…”
Section: Extraction Of Lceomentioning
confidence: 99%
“…The chemical composition, antioxidant and antimicrobial activities of LCEO, and the bioactivity of citral and limonene have been summarized . Recently, Qiu et al (2021) overviewed the total valorization of L. cubeba, covering various aspects, such as extraction, bioactivity, and purification, of LCEO. In general, the antioxidant and antimicrobial usage of LCEO in food industry is not the objective of these reviews.…”
Section: Introductionmentioning
confidence: 99%
“…L. cubeba is mainly distributed in China, Myanmar, Vietnam, Laos, Cambodia, Thailand, India, and Indonesia. In China, it generally grows in tropical and subtropical areas south of the Yangtze River [14,15]. Most L. cubeba in China grows wild, with scattered source areas, significant regional differences, and rich genetic variations.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of L. cubeba is now becoming rare, so L. cubeba status has become Least Concern ver 3.1 IUCN (Kok 2021). The leading cause of this species' scarcity is the distilling of the bark and leaves as raw materials for perfume (Qiu et al 2021). Based on these facts, it is necessary to breed L. cubeba so it does not become extinct.…”
Section: Introductionmentioning
confidence: 99%